INTRIGUING MANIFESTATION OF MILIARY TUBERCULOSIS - A CASE REPORT - Wahinuddin S,; Ainon MM,; Ng EK,; Muhaini O,; Norraha AR, (Asian Journal of Medicine & Health Sciences, 2019)
This report is a case of a 24-year-old immunocompetent lady treated with anti-tuberculous drug for disseminated tuberculosis diagnosed by bone marrow finding. She presented with concurrent intracranial and intramedullary tuberculoma associated with tuberculous spondylodiscitis evidenced by serial magnetic resonance imaging (MRI) screening after a month of anti-tuberculous therapy. These complications are thought to be paradoxical effects of anti-tuberculous therapy. Symptoms resolved with continuation of anti-tuberculous treatment and a course of corticosteroid.